2005
DOI: 10.1002/masy.200550928
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile Release of Insulin from Layer‐by‐Layer Assembled Microgel Thin Films

Abstract: We describe studies concerning the construction and characterization of insulin‐impregnated poly(N‐isopropylacrylamide‐co‐acrylic acid) microgel thin films prepared by Layer‐by‐Layer (LbL) polyelectrolyte assembly. These films can be built up in a highly uniform fashion and display linear buildup dependence even up to 30 layers. Thermoresponsivity of these drug loaded films can be utilized to obtain extended pulsatile release of insulin over many cycles. Continuous thermal pulsing allows solubilization of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…Lyon and coworkers first applied the LbL technique to self-assemble temperature-responsive NIPAAm-co-acrylic acid microgels and poly(allylamine) (PAH) on a surface. [16][17][18][19] Electrostatically self-assembled multilayers and capsules based on copolymers of NIPAAm with charged monomers were also described by Glinel et al [20] In such films and capsules, the electrostatically associated units can complex with the oppositely charged polymers, leaving the PNIPAAm segments for the thermo-responsiveness. Using PNIPAAm copolymers, Jaber et al measured expulsion of water molecules from the multilayers as a result of temperatureinduced dehydration of the PNIPAAm units, which illustrated the reversible thermal modulation of ion transport within the films.…”
Section: Introductionmentioning
confidence: 93%
“…Lyon and coworkers first applied the LbL technique to self-assemble temperature-responsive NIPAAm-co-acrylic acid microgels and poly(allylamine) (PAH) on a surface. [16][17][18][19] Electrostatically self-assembled multilayers and capsules based on copolymers of NIPAAm with charged monomers were also described by Glinel et al [20] In such films and capsules, the electrostatically associated units can complex with the oppositely charged polymers, leaving the PNIPAAm segments for the thermo-responsiveness. Using PNIPAAm copolymers, Jaber et al measured expulsion of water molecules from the multilayers as a result of temperatureinduced dehydration of the PNIPAAm units, which illustrated the reversible thermal modulation of ion transport within the films.…”
Section: Introductionmentioning
confidence: 93%
“…3). The rapid response is a merit of LbL films compared with the slower response in the insulin release from hydrogels and microcapsules [21,29]. We have previously reported that pH stability of insulin-containing LbL films under physiological temperature (37°C) is nearly comparable to that at 20°C [27,30,31].…”
Section: Ph-induced Decomposition Of Insulin Lbl Filmsmentioning
confidence: 99%
“…Recently, much attention has been devoted to the development of insulin LbL films for the development of insulin formulations that can be orally administrated [21][22][23][24][25][26]. It is very clear that oral route for drug delivery is the most convenience and desired as an invasive method of drug delivery compared to injection.…”
Section: Introductionmentioning
confidence: 99%
“…18 Mono-and multilayer structures of microgel particles loaded with therapeutic substances can serve as drug reservoirs and release these substances from the film by temperature variations. 19 A similar concept was applied to study the uptake and release of doxorubicin. 20 Moreover, microgel multilayers are also discussed as potential antifouling coatings.…”
Section: Introductionmentioning
confidence: 99%